Histological Studies of Effect of Dichlorvos on Hypothalamic-Pituitary-Testicular Axis Following the Administration of Mimosa Pudica Extract - Enye Linus Anderson; Oluwasimirin Tunde; Edem Edem; Saka Olusola S; Adekeye Adeshina (Journal of Endocrinology And Hormones, 2020)
Plants have played a significant role in maintaining human health and improving the quality of human life. Therefore, this present study seeks to evaluate the role of its alkaloid fraction in the hypothalamic-pituitary-testicular axis after dichlorvos poisoning in mice. A total of 25 male mice, weighing approximately 20-30 g, were randomly assigned into 5 groups of 5 mice each (Groups A, B, C, D and E). Mice in groups A served as control and received normal saline while groups B, C and E. received 5 mg/kg of dichlorvos daily for 14 days. Mice in group D received 200mg/ kg of Alkaloid extract of Mimosa pudica (AEMM) for 14 days. At the end of the experiment, all animals were sacrificed and Hypothalamus, Pituittary and Testes were excised for histological process. Sperm from cauda epididymidal duct on one side was collected and used for spermatological studies and data were expressed as mean± SEM. Significant difference was set at p<0.05. Results showed significance difference (p<0.05) in sperm motility, sperm life death ratio groups when compared with their controls and no significance difference in sperm volume when compared with control. Histological studies reveal distortion in hypothalamuss, pituitary and testes in dichlorvos administration group compared with control rats while mimosa showed a ameliorative effect when co-administered with dichlorvos. In conclusion, the alkaloids from Mimosa (AEM) leaves enhanced the released of gonadotropins by the cordial action of the hypothalamus-pituitary axis for the reversed of Dichlorvos effect.
Keywords: Histological studies